Asymmetric and time-horizon effects of geopolitical risk, digital assets, economic policy uncertainty, and commodity prices on Brazil’s sustainability index - Darsono, Susilo Nur Aji Cokro; Handayani, Sintia; Mutiara, Intan; Nguyen, Tran Thai Ha; Chong, Fennee; Johari, Sobar M. (Universitas Muhammadiyah Yogyakarta, 2026)
This study examines the short run and long run effects of geopolitical risk (GPR), Bitcoin (BTC) prices, economic policy uncertainty (EPU), world oil prices, world gold prices, and the Dow Jones Sustainability Index (DJSI) on Brazil’s Corporate Sustainability Index (ISE B3). Using monthly data from January 2019 to December 2024 and applying the Autoregressive Distributed Lag (ARDL) bounds testing framework, the analysis identifies asymmetric and time horizon dependent relationships. In the short run, gold prices exert a statistically significant negative effect on the ISE B3, consistent with asset substitution behaviour during periods of heightened uncertainty. By contrast, the DJSI displays a positive and significant influence, reflecting the transmission of global sustainability sentiment. In the long run, economic policy uncertainty and oil prices exert significant negative effects on the index, while geopolitical risk and Bitcoin prices have significant positive impacts. A robustness specification excluding the DJSI confirms the stability of the core results for EPU, oil prices, GPR, and Bitcoin. However, omitting the global sustainability benchmark modestly amplifies the estimated magnitudes of GPR and Bitcoin, indicating partial overlap in the channels through which global investor sentiment influences the ISE B3. These findings contribute to the emerging literature on the macro financial determinants of sustainability indices in emerging markets and provide actionable insights for portfolio managers, ESG oriented investors, and policymakers.